Design of Hybrid Superwetting Surfaces with Self‐Driven Droplet Transport Feature for Enhanced Condensation. Issue 13 (10th June 2021) - Tang, Yu; Yang, Xiaolong; Li, Yimin; Zhu, Di
Abstract: Patterned hybrid superwetting surfaces that function in drop‐film‐wise condensation mode have great potential applications in heat transfer devices, water desalination, etc., due to the high performance of condensate transport. However, design and combination strategy for pattern optimization are still not clear. In this work, superhydrophobic surfaces with wedge‐shaped superhydrophilic patterns are created for enhanced condensation. Dependence of geometry, size, and combination of the patterns on droplet transporting and heat transfer coefficient is investigated. Results imply that superhydrophobic surface with array of single‐wedge‐shaped superhydrophilic patterns shows 30% improvement of heat transfer coefficient when compared with superhydrophobic surface, due to rapid condensate transferring from drop‐wise to film‐wise region, condensate converging and departing from the film‐wise region. Additionally, when compared with the surface with array of cluster‐wedge‐shaped superhydrophilic patterns, the surface with array of single‐wedge‐shaped superhydrophilic patterns have higher condensation efficiency because of the larger total circumference, which donate greater condensate transferring capacity. Moreover, single‐wedge‐shaped superhydrophilic patterns with large size show higher heat transfer coefficient than the patterns with small size due to lower saturated vapor pressure. This new fundamental insight can be used to develop new hybrid superwetting surfaces intended on engineering applications, such as water production and heat transfer. Abstract : Hybrid superwetting surfaces with wedge‐shaped superhydrophilic patterns that can transport droplets spontaneously are designed and fabricated to enhance the drop‐wise condensation. Combination strategy of the patterns for designing an optimized surface is proposed based on dynamic behavior of droplet transporting, which has great potential applications in heat transfer devices, water desalination, etc.